Clear View Sdn. Bhd. / Im Qama Azhar Zulkifli ... [et al.] - Azhar Zulkifli, Im Qama; Mat Sebon, Mohd Faizul; T. Eddie, T. Eniwati; Wan Noor, Wan Nur Ifnani; Saaiddutdin, Siti Sarah; Ismail, Nurul Afizah (Faculty of Electrical Engineering, 2002)
The development in Malaysia are encouraging and giving us an initiative to run our own business. The business that we are going to perform is rendering a business of indoor cleaning services. The name of our business is CLEAR VIEW Shd Bhd. Beside that we also provide a indoor cleaning such as sweeping, toilet cleaning, rubbish, disposal, premises window polishing, mopping and floor buffing. We are sure that the business regarding to the indoor cleaning will give us the best income our business. Our business is planning to be made-up at No 2, Jin Badminton 13/29, Section 13, Shah Alam, Selangor. And we are planning to start this business on 1st January 2007. We are choosing this area because we found that it has high prospect to develop and the strategic area. School and working sector are our main target to earn more profit. The overview of our company is in Shah Alam due to there are not many company doing this kind of business, and this the bonus for us. So due to that it is influencing us to choose this business. Beside that our company not only focus in Shah Alam but all over Selangor also. Finally we hope that this business will give us a good potential to develop more and more.